MILITARIZATION OF SPACE AS A LEGAL CHALLENGE - Timush, Iryna; Muzychka, Ivan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to identify the gaps and shortcomings of international space law, which create opportunities and support for the militarization of space, and to formulate proposals on ways to improve the legal mechanisms for ensuring the peaceful use of space. In accordance with the set goal, the following main tasks have been defined: to analyze the main international treaties and agreements regulating the issue of space militarization; identify legal issues related to the use of outer space for military purposes. Research methods: general scientific (dialectical, analysis and synthesis, system-functional) and special legal methods (logical-legal, formal-legal, comparative-legal) were used. Results: the problem of the militarization of outer space is considered as a key legal challenge of modern times. It was emphasized that international documents in the outlined area only partially regulate the issue of using outer space for military purposes, leaving significant gaps that make it difficult to preserve its peaceful character. The main legal problems that contribute to the militarization of space are identified, in particular: the lack of clear control mechanisms for the arms race, insufficient regulation of the use of dual-use technologies, the difficulty of applying international humanitarian law to outer space, as well as the limitation of responsibility for possible military incidents in space. Modern threats related to the placement of weapons in orbit, the possibilities of attacks on space infrastructure and its impact on global security are analyzed. Ways to overcome these challenges are proposed through the development of new international legal norms and mechanisms aimed at the demilitarization of certain areas of space, the expansion of control over the activities of private space companies, as well as the adaptation of the principles of international humanitarian law to the space sphere. Discussion: the rapid development of space technologies, the growth of the number of space states and the activation of the private sector lead to the transformation of space into a strategic arena for ensuring national security. It is necessary to update the legal approach to the use of outer space, taking into account modern technological, political and security challenges. The importance of the international community in maintaining stability and security in outer space.